Feasibility of Applying Proton Minibeam Technology on the Proton Therapy Complex “Prometheus” - O.Yu. Golovanova; G.V. Merzlikin; A.D. Kaprin; A.N. Soloviev; V.O. Saburov; S.N. Koryakin (Sovremennye tehnologii v medicine, 2026)
Spatial fractionation of proton beams is being considered as a new strategy to reduce the probability of side-effects in radiation therapy on the proton therapy complex (PTC) “Prometheus”. By collimating the beams to submillimeter dimensions, the dose profile at the target surface consists of alternating high- and low-dose regions. This promotes sparing of normal tissues along the beam path through the activation of various biological mechanisms. The aim of the study was to implement the minibeam method on the PTC “Prometheus” and to experimentally assess the quality of the resulting dose distribution. Materials and Methods. Collimation of the primary beam was achieved using brass multislit collimators. Mathematical modeling of the experiment was performed, and a phantom was irradiated from one and from two opposite directions. For effective summation of two fields and to achieve a homogeneous dose distribution in the target, intensity and energy modulation of the proton beams entering the collimator was carried out. To reduce errors caused by collimator deviation relative to the beam axis, a quality assurance system for collimator positioning on the treatment table was developed. Under the control of a scintillation detector and a laser positioner, positioning accuracy was within 0.2°. GafChromic EBT3 radiochromic films (Ashland, USA) were used as dosimeters. Results. When comparing calculated and experimental data, 90% of the distribution points matched the mathematical model according to the γ criterion (3%/3 mm). The quality of the minibeam field was assessed using the following parameters: valley-to-peak dose ratio; collimator throughput; ratio of the dose without the collimator to the dose with the collimator; and dose homogeneity index in the target. The obtained results met the quality assurance criteria for standard radiation therapy. Conclusion. Irradiation with proton minibeams using brass collimators is feasible on the PTC “Prometheus”. A uniform dose distribution in the target area was experimentally achieved. The uniformity of coverage, the absence of local dose excesses, and the high dose gradient at the distal edge suggest that the described irradiation technique can be implemented on biological specimens.